Contribution to the knowledge of the genus Omineus Lewis, 1895 in Taiwan, with description of two new species (Coleoptera, Mycteridae, Eurypinae) - Hsiao, Yun; Pollock, Darren A. (Zootaxa, 2019)
The fauna of Mycteridae Blanchard, 1845 in Taiwan is small, with only two documented species. In the present paper, two new species of Omineus Lewis, 1895 are described: O. taiwanensis sp. nov. and O. chuangae sp. nov., highlighting the potential diversity of this family in Taiwan. New species descriptions are supplemented with photographs and illustrations of habitus and salient structures of both sexes. A key for the identification of Omineus species in Taiwan is provided.